Hot carriers perspective on the nature of traps in perovskites - Righetto, Marcello (2022)
Amongst the many spectacular properties of hybrid lead halide perovskites, their defect tolerance is regarded as the key enabler for a spectrum of high-performance optoelectronic devices that propel perovskites to prominence. However, the plateauing efficiency enhancement of perovskite devices calls into question the extent of this defect tolerance in perovskite systems; an opportunity for perovskite nanocrystals to fill. Through optical spectroscopy and phenomenological modeling based on the Marcus theory of charge transfer, we uncover the detrimental effect of hot carriers trapping in methylammonium lead iodide and bromide nanocrystals. Higher excess energies induce faster carrier trapping rates, ascribed to interactions with shallow traps and ligands, turning these into potent defects. Passivating these traps with the introduction of phosphine oxide ligands can help mitigate hot carrier trapping. Importantly, our findings extend beyond photovoltaics and are relevant for low threshold lasers, light-emitting devices and multi-exciton generation devices.